2015
DOI: 10.1109/lpt.2015.2453968
|View full text |Cite
|
Sign up to set email alerts
|

Widely Tunable Amplified Feedback Laser With Beating-Frequency Covering 60-GHz Band

Abstract: A monolithic integrated amplified feedback laser is experimentally demonstrated as a new solution to generate dual-mode lasing with a wide frequency tuning range covering the entire 60-GHz band. This laser consists of a complex-coupled distributed feedback laser (DFB) and an integrated feedback cavity formed by a phase section and an amplifier section. Different laser sections are integrated by a simple quantum well intermixing (QWI) technique. By tuning the injection currents of the laser sections, the beatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The tuning range of this OEO scheme is determined by the frequency tuning range of the AFL. Since the AFL-structure can work in other frequency ranges, like 10-GHz, 20-GHz, and 60-GHz, through choosing appropriate cavity length [22]- [24], the proposed OEO scheme can be easily extended to many other frequency-bands. Moreover, it is also technologically possible to integrate the optical coupler, resonator and the PD with the AFL to form a single chip OEO.…”
Section: Resultsmentioning
confidence: 99%
“…The tuning range of this OEO scheme is determined by the frequency tuning range of the AFL. Since the AFL-structure can work in other frequency ranges, like 10-GHz, 20-GHz, and 60-GHz, through choosing appropriate cavity length [22]- [24], the proposed OEO scheme can be easily extended to many other frequency-bands. Moreover, it is also technologically possible to integrate the optical coupler, resonator and the PD with the AFL to form a single chip OEO.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the amplitude imbalance and the lack of coherence of the two laser modes, the temporal waveform does not show a well-defined sinusoidal shape, and the corresponding phase portrait also shows a limit cycle feature, but the traces are broadened compared to the P1 state. In our previous work [7,25,26], we have theoretically and experimentally demonstrated that in the dual-mode state, the beating frequency of the AFL's emission increases with the increase of the feedback strength as I A increases. The relationship between the frequency of the on-chip generated microwave signal and I A of the integrated laser-photodetector chip was investigated by increasing I A from 24.5 mA to 50.5 mA with a 2-mA step.…”
Section: Dynamic Statesmentioning
confidence: 91%